Examining The Impact Of Work–Family Conflict And Work–Life Balance On Female Caddies’ Performance: Evidence From PT X Surabaya - Windy Permatasari; Mei Retno Adiwati (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study analyzes the effects of Work–Family Conflict and Work–Life Balance on the performance of female caddies at PT X in Surabaya City, aiming to understand the impact of dual-role pressures on employee performance and to support the development of effective human resource management strategies. Methodology: A quantitative research design was employed using a survey approach. Structured questionnaires were distributed to 58 married female caddies selected through a total sampling technique. The collected data were analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM). Results: The results indicate that Work–Family Conflict has a negative and statistically significant effect on employee performance (β = –0.477; p < 0.05). In contrast, Work–Life Balance shows a positive and significant effect on employee performance (β = 0.430; p < 0.05). Findings: These findings confirm that dual-role pressures and life equilibrium are critical determinants of performance outcomes. Novelty & Originality: This study provides empirical evidence by focusing on female caddies, an occupational group within the service industry that remains relatively underexplored in previous studies. Conclusions: The findings emphasize the importance of minimizing Work–Family Conflict and strengthening Work–Life Balance to improve employee performance through supportive organizational policies. Type of Paper: This paper is a research article.